Immediate reconstruction of nasal alar defects after malignant skin tumor excision without mohs surgery - Tapan, Mehmet; Özkan, Özlenen (The European Research Journal, 2023)
Objectives: The National Comprehensive Cancer Network guidelines state that any nasal region with squamous or basal cell skin cancer is at high risk. Although Mohs surgery is the gold-standard procedure for many types of skin cancer, it is not applicable worldwide. A mean of 1.7 Mohs surgery stage is performed in cases of tumors. Nasal obstruction is a problem with Mohs surgery. In this study, we aimed to investigate nasal alar region nonmelanoma malignant skin tumor excision using immediate reconstruction without Mohs surgery. Methods: Ten patients underwent reconstruction surgery between 2018 and 2022. The inclusion criterion were ulcerated lesions in the nasal alar region measuring less than 1 cm in diameter, the lesions which were suspected either as basal cell carcinoma (BCC) or squamous cell carcinoma (SCC) on dermatoscopic examination, the patients who had intact nasal mucosa during anterior rhinoscopy. Results: The mean follow-up duration was 26 months. No patient required re-operation because of an excisional biopsy result that involved border proximity. We observed no serious complications or long-term recurrences. Conclusion: We recommend our algorithm for patients for whom Mohs surgery is not applicable.